Aberrations in peripheral B lymphocytes and B lymphocyte subsets levels in Parkinson disease: a systematic review - Ma, Hongxia; Wang, Ziyuan; Yu, Miao; Zhai, Yibo; Yan, Junqiang (Frontiers in Immunology, 2025)
ObjectiveThe association of B lymphocytes and B lymphocyte subsets and Parkinson’s disease (PD) is increasingly acknowledged. However, there is inconsistence in the alterations of B lymphocytes or B lymphocyte subsets in peripheral blood of PD patients. To comprehensively understand its changes in PD patients,it is necessary to conduct a systematic review on this subject.MethodsPubMed, Cochrane Library, and MEDLINE databases were searched until 3rd February 2024.ResultsWe included 20 studies (n=2658) to conduct this systematic review. We conducted a qualitative analysis to assess the alterations of B lymphocytes and B lymphocyte subsets in the peripheral blood of individuals with PD. And studies reviewed demonstrated a significant decrease in the number of B cells, as well as immune dysregulation in the B lymphocyte subsets of these patients’ peripheral blood.ConclusionStudies reviewed demonstrated that PD is linked to abnormalities in B lymphocytes and/or B lymphocytes subsets in peripheral blood. This study provides a novel perspective into the pathogenesis of PD, and future investigations into the B lymphocytes and/or B lymphocyte subsets as biomarkers and therapeutic targets for PD is warranted.